Sharia-Based Regional Regulations and Inter-Religious Relations in Bulukumba South Sulawesi - Ashadi L Diab (Graduate Program of Pontianak Institute of Islamic Studies, 2016)
The background for the emergence of the idea of applying Sharia based regional regulations in Bulukumba is influenced by three factors: history, politics and socio-religious reality of the community. The response to the application of Islamic law also varies. At least in broad outline there are four kinds of responses, i.e. accepting, accepting with certain conditions, refusing then accepting and refusing. The application of Islamic law in Bulukumba has caused changes both in the physical appearance and socio-religious interaction of the people. Changes in physical appearance can be seen from the increasing number of women wearing hijab and a number of writings of religious nuances in various corners of the city. Changes in the areas of social interaction can be seen from the decrease of the crime rate. In the interaction between religious communities, the Sharia-based regulations are a medium for the Islamization of society. The existence of such legislation has also left no space for non-Muslims to build or add a new place of worship.